Research on new frameworks and key technologies for intelligent emergency command communication networks - Li WANG; Aiguo FEI; Ping ZHANG; Lianming XU (Tongxin xuebao)
The new generation of emergency command communication network is the basic means and important support for enhancing China’s emergency response capabilities such as national natural disasters and accidents, and is a key component of establishing a scientific emergency management technology system.Focusing on the requirements of communication, navigating, and sensing capabilities in “intelligent emergency”, a theoretical method and framework for intelligent emergency command and communication networks was proposed, which was introduced from three aspects in terms of network deployment, resource allocation, and assisted decision-making.The difficulties and technical ideas of multi-objective dynamic network deployment for communication, navigating, and sensing, multi-dimension efficient resource allocation for communication, computation, and caching, and multi-level decision-making and intelligent enhancement with cloud-edge-terminal collaboration were analyzed and discussed.It provides theoretical methods and key technical supports for building a new generation of emergency command and communication network in China.